The developmental stage of inactivation of rye origin rRNA genes in the embryo and endosperm of wheat x rye F1 hybrids - Castilho, A. (1995)
To identify the developmental stage during which the preferential inactivation of rRNA genes from the rye parent occurs in wheat x rye hybrids, nucleolar activity was evaluated in the embryo and endosperm of developing seeds of the hybrids. The hybrids were obtained from crosses of euploid and aneuploid lines of hexaploid wheat, Triticum aestivum cv. Chinese Spring, with rye, Secale cereale cv. Centeio do Alto. The number of nucleolar organizing regions (NORs) and nucleoli present in the embryo and endosperm cells of wheat, and wheat × rye F1 hybrids, at different times after fertilization was scored by silver staining. The inactivation of rDNA of rye origin in F1 hybrids occurs simultaneously in the embryo and in the endosperm between 4 and 5 days after fertilization, when these have been through six and 10 cell cycles respectively. We conclude that the genomic interactions leading to the inactivation of the rye origin rDNA is a time-dependent process, related to the developmental stage and independent of the number of cell cycles (DNA replication rounds) they have been through.